25 Years of Transformations of Higher Education Systems in Post-Soviet Countries Reform and Continuity - Huisman, Jeroen; Smolentseva, Anna; Froumin, Isak (Springer Nature, 2018)
USSR countries; Soviet higher education reform; Soviet higher education policy; Post-Soviet higher education; vertical system differentiation; horizontal system differentiation